Impact of International legal Policy on Green Economy - Siregar, Rahmad Ramadhan; Alfan Dzikria Nurrachman; Peter Guntara (International Journal of Law and Legal Ethics, 2025)
This research examines the urgency of international legal policy in promoting sustainable development and the transition to a green economy, given global challenges such as climate change and environmental degradation that require a collective response. The aim is to analyze the effectiveness of international legal instruments, such as the Paris Agreement and the SDGs, in creating a regulatory framework that supports a green economy. This research uses a normative juridical method with analysis of international legal documents and case studies to evaluate the implementation of these policies. The results show that international legal policies have played an important role in setting global standards for sustainable development, but their implementation still faces challenges such as inconsistencies in national regulations and lack of effective enforcement mechanisms. In conclusion, while the international legal framework has provided a solid foundation, it requires policy harmonization, institutional capacity building and stronger political commitment from member states. Suggestions include strengthening monitoring mechanisms, improving technology transfer and funding, and integrating green economy principles into national development policies.